2016
DOI: 10.20321/nilejbe.v1i1.44
|View full text |Cite
|
Sign up to set email alerts
|

Macroeconomic Determinants of Industrial Development in Nigeria

Abstract: <p>The paper focuses on the impact of macroeconomic determinants on industrial productivity in Nigeria for the period, 1981-2013. It was discovered that while the Nigerian government had embarked on a number of industrial development strategies with the sole purpose of boasting industrial productivity in Nigeria, they seem to have yielded little or no result. The macroeconomic variables in the study include industrial production index, exchange rate, consumer price index, interest rate, broad money suppl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…They stressed that for the manufacturing sector to function effectively as a strategic propeller of economic growth the problems mentioned above have to be tackled. In a related study conducted for Nigeria on macroeconomic determinants of industrial development [10] observed that the Nigerian government had embarked on several industrial programmes with the goal of boasting industrial productivity but all effort have failed to yield the required positive result.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They stressed that for the manufacturing sector to function effectively as a strategic propeller of economic growth the problems mentioned above have to be tackled. In a related study conducted for Nigeria on macroeconomic determinants of industrial development [10] observed that the Nigerian government had embarked on several industrial programmes with the goal of boasting industrial productivity but all effort have failed to yield the required positive result.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The result shows that at 10 percent level, prime lending and deposit rate respectively have positive and negative effects on industrial output. Although positive impact of prime lending on the productivity of the industrial sector is noteworthy as it deviated from the a priori expectation, it authenticated past studies (Aiyedogbon and Anyanwu, 2016;and Dada, 2015), but conflicted with Imoisi (2012). However, this could be attributed to the poor development of the financial system and inconsistencies that often characterize the implementation of monetary policy in Nigeria.…”
Section: Estimation Of the Ardl Modelmentioning
confidence: 61%
“…The study concludes that financial accelerator mechanism is more effective during periods of recession. Aiyedogbon and Anyanwu (2016) examined the macroeconomic determinants of industrial development in Nigeria between 1981 and 2013. The study included exchange rate, consumer price index, broad money supply, and interest rate among others in the model as determinants of industrial production index.…”
Section: Review Of Empirical Literaturementioning
confidence: 99%
“…The findings contradict the empirical work of (Ogunsanya et al, 2017) which revealed a positive and significant relationship between gross domestic product (GDP) and agricultural output in Nigeria. The results are also not in line with the work of Aiyedogbon & Anyanwu, (2015), showed that industrial productivity itself has failed to yield the required positive result.…”
Section: Short-run Analysismentioning
confidence: 63%
“…Studies have also revealed that it is not only price-related factors but also investment, human capital, income levels, manufacturing export and industrial output have not reached the desired threshold to achieve economic growth (Dan &Wanjuu, 2016;Joseph et al, 2019) but the empirical study of Aiyedogbon & Anyanwu, (2015), which examined the macroeconomic determinants of industrial development, showed that industrial productivity itself has failed to yield the required positive result. Moreover, the effect of industrial development on economic performance was appalling which was necessitated by the intermittent electricity supply in Nigeria (Udah, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%